Manajemen Dakwah Takmir Masjid Jogokaryan dalam Membangun Peradaban Islam di Mantrijeron Yogyakarta - Arsam, Arsam; Nurmahyati, Siti; Amaluddin, Asep (Tadbir: Jurnal Manajemen Dakwah, 2024)
This paper describes the management of the preaching of the takmir of the Jogokaryan mosque in building Islamic civilization. The background is about the empirical condition of the mosque which is not functioning according to expectations as was the time of the prophet Muhammad SAW and his companions. The mosque is only used as a place for ritual worship activities, even having the impression that the mosque is only a symbol of the existence of Muslims in an area and not a solution for the people. The purpose of this study was to determine the management of preaching takmir at the Jogokaryan mosque in building Islamic civilization in Jogokaryan Mantrijeron, Yogyakarta. The research method used is descriptive qualitative method. While the data analysis used in this study is the method of analysis of Mile and Huberman. The results of the study concluded that the management of the Jogokaryan Mosque can be categorized as having a level of success in building Islamic civilization, namely by carrying out da'wah management functions, namely: 1) Da'wah planning which includes da'wah mapping, service, empowerment and coaching. 2) Organizing da'wah activities. 3) implementation by moving the person in charge of the activity. 4) Supervision of da'wah, namely monitoring or monitoring da'wah activities. The Da'wah management activities are carried out continuously and continuously.